Investing in farmers: Agriculture human capital investment strategies - Davis, Kristin E.; Gammelgaard, Johanna; Preissing, John; Gilbert, Rachel; Ngwenya, Hlamalani (Food and Agricultural Organization of the United Nations, 2021)
Investing in farmers – or agriculture human capital – is crucial to addressing challenges in our agri-food systems. A global study carried out by the FAO Investment Centre and the International Food Research Institute, with support from the CGIAR Research Programme on Policies, Institutions and Markets and the FAO Research and Extension Unit, looks at agriculture human capital investments, from recent trends to promising initiatives in Cameroon, Chile, Côte d’Ivoire, India, Indonesia, Kenya, Peru, Rwanda and the United States of America. It also includes 11 shorter case studies, ranging from pastoralist training centres to the inclusion of indigenous communities. The global study aims to provide governments, international financing institutions, the private sector and other partners with the evidence and analysis needed to make more and better investments in agriculture human capital. This publication is part of the Directions in Investment series under the FAO Investment Centre's Knowledge for Investment (K4I) programme.